2005
DOI: 10.1113/jphysiol.2005.098053
|View full text |Cite
|
Sign up to set email alerts
|

Kv1 channels selectively prevent dendritic hyperexcitability in rat Purkinje cells

Abstract: Purkinje cells, the sole output of the cerebellar cortex, encode the timing signals required for motor coordination in their firing rate and activity pattern. Dendrites of Purkinje cells express a high density of P/Q-type voltage-gated calcium channels and fire dendritic calcium spikes. Here we show that dendritic subthreshold Kv1.2 subunit-containing Kv1 potassium channels prevent generation of random spontaneous calcium spikes. With Kv1 channels blocked, dendritic calcium spikes drive bursts of somatic sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 75 publications
(120 reference statements)
0
45
0
Order By: Relevance
“…This result highlights the importance of Kv1 channels in shaping the complex spike, although block of Kv1 channels cannot account for the effects of TEA because DTX-K caused only minor changes in complex spike properties. Kv1 channels selectively regulate dendritic excitability of PCs (Khavandgar et al, 2005), and therefore this result highlights the importance of certain dendritic conductances in shaping the somatic complex spike waveform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result highlights the importance of Kv1 channels in shaping the complex spike, although block of Kv1 channels cannot account for the effects of TEA because DTX-K caused only minor changes in complex spike properties. Kv1 channels selectively regulate dendritic excitability of PCs (Khavandgar et al, 2005), and therefore this result highlights the importance of certain dendritic conductances in shaping the somatic complex spike waveform.…”
Section: Resultsmentioning
confidence: 99%
“…We found that blocking DTX-sensitive Kv1 channels, which are thought to be expressed in PC dendritic membranes and absent from somas (Southan and Robertson, 2000;Khavandgar et al, 2005) (but see McKay et al, 2005), dramatically compromised robust repetitive spikelet activity without affecting repolarization of the first spike (Fig. 2).…”
Section: Ionic Mechanisms Of Generation Of the Complex Spikementioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, as for Na v channels, it is likely that the AIS clustering of Kv1 channels is a multistep sequence of events, including directed trafficking to the axon followed by retention of channels at the AIS by PSD-93. Although we have focused on their AIS localization, Kv1 channels can also be detected along unmyelinated axons and in somatodendritic domains depending on the neuron (Trimmer and Rhodes, 2004;Khavandgar et al, 2005). Therefore, additional mechanisms regulating Kv1 channel localization in neurons remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy, however, that the contribution of active conductances can be remarkably balanced, allowing for linear summation of inputs, such as in CA1 pyramidal neurons (Cash and Yuste, 1999). We believe that the latter scenario also applies to Purkinje cells given their linear input-output function and the fact that blockade of subthreshold voltage-gated Kv1-type potassium channels significantly affects the amplitude and time course of somatic depolarizations evoked by a range of synaptic-like inputs (Khavandgar et al, 2005). The contribution of these channels is likely to be balanced by active conductances such as P/Q-type voltage-gated calcium channels, which are present at a high density in the dendrites of Purkinje cells (Usowicz et al, 1992).…”
Section: Comparison With Other Neuronsmentioning
confidence: 99%